Safety and immunogenicity of an intranasal sendai virus-based vaccine for human parainfluenza virus type I and respiratory syncytial virus (SeVRSV) in adults. Issue 2 (1st February 2021) - Scaggs Huang, Felicia; Bernstein, David I.; Slobod, Karen S.; Portner, Allen; Takimoto, Toru; Russell, Charles J.; Meagher, Michael; Jones, Bart G.; Sealy, Robert E.; Coleclough, Christopher; Branum, Kristen; Dickey, Michelle; et al.
ABSTRACT: SeVRSV is a replication-competent Sendai virus (SeV)-based vaccine carrying the respiratory syncytial virus (RSV) fusion protein (F) gene. Unmanipulated, non-recombinant SeV is a murine parainfluenza virus type 1 (PIV-1) and serves as a Jennerian vaccine for human PIV-1 (hPIV-1). SeV protects African green monkeys (AGM) from infection after hPIV-1 challenge. The recombinant SeVRSV additionally targets RSV and protects AGM from lower respiratory infections after RSV challenge. The present study is the first to report on the safety, viral genome detection, and immunogenicity following SeVRSV vaccination of healthy adults. Seventeen and four healthy adults received intranasal SeVRSV and PBS, respectively, followed by six months of safety monitoring. Virus genome (in nasal wash) and vaccine-specific antibodies (in sera) were monitored for two and four weeks, respectively, post-vaccination. The vaccine was well-tolerated with only mild to moderate reactions that were also present in the placebo group. No severe reactions occurred. As expected, due to preexisting immunity toward hPIV-1 and RSV in adults, vaccine genome detection was transient. There were minimal antibody responses to SeV and negligible responses to RSV F. Results encourage further studies of SeVRSV with progression toward a clinical trial in seronegative children. Abbreviations: AE-adverse event; SAE-serious adverse event; SeV-Sendai virus; RSV-respiratory syncytial virus; PIV-1-parainfluenza virus-type 1; hPIV-1-human parainfluenza virus-type 1; F-RSV fusion protein; SeVRSV-recombinant SeV carrying the RSV F gene; Ab-antibody; MSW-medically significant wheezing; NOCMC-new onset chronic medical condition, mITT-modified Intent to Treat; ALRI-acute lower respiratory tract infection.